The Development of Leisure Participation Assessment Tool for the Elderly - Eun-Hwa Jeong; Eun-Young Yoo; Jong-Bae Kim; Jung-Ran Kim; Dae-Sung Han; Ji-Hyuk Park (Occupational Therapy International)
Objectives. This study is aimed at developing multidimensional leisure participation assessment tool for the elderly to achieve quantitative and qualitative assessment of leisure participation and leisure exploration. Methods. This study collected preliminary items through literature review, statistical office data, and survey of the elderly’s leisure activities and considered the list of leisure activities as assessment items by conducting a Delphi survey. Reliability was verified through internal consistency and test-retest reliability. The assessment tool was finally confirmed using content validity and discriminant validity. Results. A total of 81 leisure items classified into 8 categories and 22 subcategories were obtained through data collection and Delphi survey. Cronbach’s α value was 0.939, and Intraclass Correlation Coefficient was 0.941. A content validity test was confirmed by validating that I-CVI was 0.78 or more and the S-CVI was 0.95. According to the result of discriminant validity, there was a difference in the number of participating leisure activities and leisure activities with participation intention by age. Conclusion. The leisure participation assessment tool for the elderly developed in this study can obtain information on the overall view of the leisure of the elderly by measuring leisure exploration, leisure participation, and interference factor affecting leisure participation.